Autonomous Learning in English Class - Azizah, Nur; Kardena, Absharini (Darul Yasin Al Sys, 2023)
In the Indonesian educational system, autonomy has been demanded to be promoted in the teaching and learning process of recent curriculum implementation. Unfortunately, it cannot be denied that learner autonomy still poses a challenge to be implemented in Indonesia since the teaching-learning process still was dominant. Therefore, it is essential to explore students’ problems with learner autonomy. This study used descriptive quantitative study through the questionnaire as the students’ data collection method, to explore students’ problems with autonomous English Learning. Ninety one students from one of MAN in Agam were involved to elicit their problems on autonomous English learning. Furthermore, this finding showed that the students have problems with autonomous English learning. This study found problems of students in autonomous English learning which were (1) developing the target language into a separate reference system and being willing to revise and reject hypotheses and rules that do not apply, (2) willing to take risks, (3) and good guessers. On other hand, the study showed four indicators were low problematic. There were (1) The students should have a tolerant and outgoing approach to the target language, (2) The learners take an active approach to the learning task at hand, (3) Autonomous learners have insights into their learning styles and strategies, and (4) The learners try to be proactive in developing their ability in English by seeking external knowledge. The learners who try to be proactive in developing their ability in English by seeking external knowledge are the least students who answered.